1997
DOI: 10.1002/etc.5620161029
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity of individual polycyclic aromatic hydrocarbons and petroleum to marine invertebrate larvae and juveniles

Abstract: Abstract-Phototoxicity resulting from photoactivated polycyclic aromatic hydrocarbons (PAHs) has been reported in the literature for a variety of freshwater organisms. The magnitude of increase in PAH toxicity often exceeds a factor of 100. In the marine environment phototoxicity to marine organisms has not been reported for individual or complex mixtures of PAHs. In this study, larvae and juveniles of the bivalve, Mulinia lateralis, and juveniles of the mysid shrimp, Mysidopsis bahia, were exposed to individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
115
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(121 citation statements)
references
References 30 publications
3
115
1
Order By: Relevance
“…The phototoxicity can be more than 100-fold higher than their toxicity in the absence of light irradiation [52,53]. Yan et al [54] …”
Section: Photocytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The phototoxicity can be more than 100-fold higher than their toxicity in the absence of light irradiation [52,53]. Yan et al [54] …”
Section: Photocytotoxicitymentioning
confidence: 99%
“…It has also been reported that upon light irradiation, PAHs exhibit phototoxicity [17]. Thus, photoirradiation of PAHs can be an activation pathway and may play an important role on skin cancer [23][24][25][26]. However, this pathway has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one previous study Fern andez-Tajes et al [19] showed a higher sensitivity of clams and cockles to pollution load levels. Additionally, results from Pelletier et al [60] indicated that the glochidial larvae of Utterbackia imbecillis are sensitive to photoactivated pyrene at environmentally [29]. Increases in total GSH concentrations reflect an up-regulation of antioxidant defenses [36].…”
Section: Antioxidant Responses Of P Martensii To Pyrenementioning
confidence: 99%
“…There have been studies on the photo-induced toxicity of PAH mixtures or individuals in the marine sediment toward micro-organisms and plants in the aquatic systems (Pelletier et al 1997;Swartz et al 1997).…”
mentioning
confidence: 99%
“…The increase in toxicity due to ssr can exceed 100 times (Swartz et al, 1997). It is suggested that PAHs act as photosensitizers (Pelletier et al 1997). After absorbing UV light energy, PAHs in the excited-state may transfer its energy to molecular oxygen to produce reactive oxygen species that can cause a variety of damages to the cell.…”
mentioning
confidence: 99%